Prognostic and clinicopathological roles of circular RNA expression in chemoresistance in head and neck squamous cell carcinoma: a systematic review - Das, Sayan Kumar; Khasbage, Sameer; Mishra, Ashim; Jee, Babban (Frontiers in Pharmacology, 2025)
BackgroundCharacterized by a poor prognosis and survivability, head and neck squamous cell carcinoma (HNSCC) is an aggressive neoplastic condition with a propensity for recurrence where the development of chemoresistance adversely affects the prognostic outcome. Recently, it was shown that circular RNAs (circRNAs) augment the cellular survivability and chemoresistance of malignant cells. Hence, biomarkers for early detection of chemoresistance in these patients can significantly aid in preventing a poor prognostic outcome.ObjectiveThe present study aimed to systematically identify circRNAs that play a vital role in the development of chemoresistance in HNSCC and understand their mechanisms of action in HNSCC chemoresistance.MethodsThe protocol was prospectively registered on PROSPERO with protocol no. CRD42024532291. A six-stage methodological and PRISMA recommendations were followed for the review.Results and Discussion13 studies were identified which yielded 13 circRNAs which have been investigated for their role in the chemoresistance in HNSCC. Of these, 11 circRNAs were reported to be upregulated while only 2 circRNAs were found to be downregulated. Moreover, we found that circRNAs can modulate autophagy (circPARD3, circPKD2, circAP1M2 and circPGAM1), apoptosis (circ-ILF2, circANKS1B, circTPST2, circPUM1 and circ_0001971), drug efflux (circ-ILF2, has_circ_0005033 and circTPST2), EMT (circANKS1B, circCRIM1, circ_0001971), tumor microenvironment (circ-ILF2. circ-ILF2, circCRIM1 and circTPST2), DNA damage (circTPST2) and malignant potential (hsa_circ_0000190 and hg19_ circ_0005033).ConclusionThe present study identified 13 circRNAs which may serve as biomarkers for prognosis as well as response to chemotherapy in HNSCC.Systematic Review RegistrationPROSPERO, identifier CRD42024532291.